Religious Development for Youth Ar-Rohmah Mosque - Supaih, Cici; Tabroni, Imam (Asian Journal of Community Services, 2022)
The rapid development of technology and the influence of the environment play a very important role in shaping the personality of adolescents. There are many cases involving adolescents, this becomes a problem in the process of religious education for adolescents. Therefore, the Ar-Rohmah Mosque Youth Association (IRMAR) was formed which aims to prevent them from this influence. This study aims to carry out religious coaching to youth of the Ar-rohmah mosque through religious programs. Data analysis used descriptive qualitative analysis with a mix method approach with Participatory Action Research (PAR) design. Based on the results of the study it was found that the pattern of religious development for youth at the Ar-Rohmah mosque, the point of emphasis is coaching through religious programs such as recitations of the Qur'an, Marawis Training, Adhan Training, and Muhadharah. The conclusion from the implementation of this activity is that through intensive coaching it is able to foster youth interest in prospering the mosque through the religious programs that are held. In addition, the holding of religious programs has a significant influence on religious behavior such as a sense of responsibility, independence, and courage. This can be seen in the consistent level of youth attendance at the mosque. Then by establishing good communication between related parties, such as the management of the Ar-Rohmah mosque, youth coaches of the Ar-Rohmah mosque and other community leaders, which is really needed to create teenagers who are able to work and innovate in positive activities.